Between Chester and Capetown: Transformations of the Gospel in Son of Man by Mark Dornford-May - Zwick, Reinhold (The journal of religion and film, 2011)
The African Jesus-Movie Son of Man (RSA 2006) by Mark Dornford-May crosses many boarders of genre and style and gains its unique energy by blending different sources – such as medieval mystery plays, biblical gospels or motifs of the Anti-Apartheid-Movement – into a unique, transcultural actualization of the Jesus story. A closer examination of the various connections to Pier Paolo Pasolinis’ Il Vangelo Secondo Matteo further clarifies the specific profile of Son of Man and its position within the genre of bible-movies.